Rancang Bangun Alat Estimasi Nilai Lumen Lampu Berbasis Internet of Things dengan Aplikasi Android Blynk - Ardiansah, Feri; Prasetia, Vicky; Susanti, Hera; Rafiq, Arif Ainur; Riyanto, Sugeng Dwi (Infotekmesin, 2026)
The development of lighting technology, particularly LED lamps, drives the need for light intensity testing (lumen) to ensure quality and energy efficiency. The SNI IEC 62612:2016 standard establishes testing parameters that must be met, but field testing processes are still largely manual and inefficient. This research aims to design and realize an Internet of Things (IoT)-based lamp lumen value testing tool with results displayed on an Android application as a practical and automated solution. The tool is designed according to the SNI IEC 62612:2016 standard, equipped with a BH1750 sensor to measure light intensity (lux), a PZEM-004T sensor to measure voltage and current, and an MLX90614 sensor to measure lamp surface temperature. The testing process is performed automatically using a NodeMCU ESP32 microcontroller, with measurement results displayed on a 20x4 LCD and transmitted to the Blynk application on Android in real-time. Testing on 16 LED lamp samples from various brands and powers showed that the system has high accuracy with average BH1750 sensor accuracy of 98.78%, MLX90614 sensor accuracy of 99.74%, PZEM-004T sensor accuracy for voltage of 99.9% and current 100%, as well as error-free data transmission to Android applications. This tool successfully performs lumen testing automatically, accurately, and efficiently according to national standards.